(untitled) (Scientific journal of the Fergana State University, 2024)
The article covers the artistic expression of nationality in the work of Nazar Eshanqul and the psychological analysis possibilities of this nationality. The fact that national heroes were constantly persecuted during the Soviet era is an important literary formula, expressed in deep metaphorical psychological skills, which defines the important core of the work of such boldly searching, nationalist writers. analyzes are presented. The most urgent issue that attracts attention in the center of creative products of the talented artist-writer Nazar Eshonqul is the national character and the fate of its slaves, who tragically died in the atmosphere of evil, mainly during the Soviet era. Therefore, it is not for nothing that nationality and the fate of the national image are in the center of attention in the works dedicated to the research of Nazar Eshanqul’s works. The fact that the national heroes were constantly persecuted during the Soviet era is expressed in an important literary formula, deep metaphorical psychological skill, which determines the important core of the creativity of such boldly seeking, nationalist writers. The writer’s thoughts have their own truth as they reflect not only on local literature, but also on current issues facing world literature. In this place, the negative impact of man-made development, even popular culture, Western treatment and attitude on the development of national consciousness and national character is highlighted.